In-situ manganese-doped modified silicon-oxygen negative electrode material, and preparation method and application thereof
Patent Information
- Application Number
- CN202611189259.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-30
AI Technical Summary
然而,这些改性方法多在SiO制备完成后进行,存在工艺步骤较多、改性元素分散不均、易团聚及改性效果稳定性不足等问题,且通常难以同时兼顾首次库伦效率和循环稳定性的提升
本发明提供了一种原位锰掺杂改性硅氧负极材料的制备方法,将硅废料、二氧化硅和金属锰(Mn)混合均匀后成型并干燥,并在真空条件下加热,使硅废料与二氧化硅反应生成SiO蒸气,金属Mn同步迁移并与SiO蒸气共冷凝沉积,得到原位锰掺杂改性SiO复合负极材料。所制得材料中Mn分散于SiO基体中,并形成含锰硅酸盐相和锰硅合金相。其中,含锰硅酸盐相能够调节Si-O结构,减少首次嵌锂过程中的不可逆锂消耗,同时缓解体积变化,增强结构稳定性,提高循环寿命,锰硅合金相能够改善电子传输能力,从而提高材料的首次库伦效率和循环性能。即,Mn是在SiO生成过程中原位参与反应,并形成特定Mn-Si-O/Mn-Si结构相,改变了SiO材料内部结构和组成,因此产生不同于简单掺杂的结构调控效果。与现有技术相比,本发明方法工艺简单、成本较低、SiO产率较高,且所得材料能够同时改善首次库伦效率和循环稳定性,适用于锂离子电池负极材料。
Smart Images

Figure CN123002857A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery anode material technology, and in particular to an in-situ manganese-doped modified silicon-oxygen anode material, its preparation method and application. Background Technology
[0002] Lithium-ion batteries, due to their high energy density and good cycle stability, have been widely used in portable electronic devices, new energy vehicles, and energy storage devices. With the development of high-energy-density lithium-ion batteries, traditional graphite anode materials, with a theoretical specific capacity of only 372 mAh / g, are no longer sufficient to meet application requirements. Silicon-based materials have attracted widespread attention due to their high theoretical specific capacity. Among them, silicon suboxide (SiO) combines high specific capacity with relatively better structural stability than elemental silicon, and is considered one of the promising anode materials for lithium-ion batteries.
[0003] In existing technologies, the main methods for preparing SiO materials include high-temperature oxidation, vacuum evaporation and condensation, and disproportionation reaction. While these methods can produce SiO materials, they typically suffer from problems such as demanding process conditions, high energy consumption, low yield, or insufficient product stability. Furthermore, the prepared SiO materials often exhibit low initial coulombic efficiency and insufficient cycle stability. To address these issues, existing technologies typically employ modification methods such as element doping, coating, or composites to modify SiO materials. However, these modification methods are mostly performed after SiO preparation, resulting in numerous process steps, uneven dispersion of modifying elements, easy agglomeration, and insufficient stability of the modification effect. Moreover, they usually cannot simultaneously improve both initial coulombic efficiency and cycle stability.
[0004] Therefore, existing technologies still need to provide a method for preparing SiO composite anode materials that is simple in process, low in cost, has a high SiO yield, and can simultaneously improve the first coulombic efficiency and cycle stability. Summary of the Invention
[0005] The purpose of this invention is to provide an in-situ manganese-doped modified silicon-oxygen anode material, its preparation method and application, so as to prepare a modified silicon-oxygen anode material with high yield and simultaneously take into account the first coulombic efficiency and cycle stability.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing an in-situ manganese-doped modified silicon-oxygen anode material, comprising the following steps: S1. Silicon waste, silicon dioxide and metallic manganese are mixed, pressed into a preform, and dried to obtain a pre-reaction mixture; S2. Under vacuum conditions, the pre-reaction mixture is sequentially subjected to heat preservation vaporization and condensation deposition to obtain in-situ manganese-doped modified silicon-oxygen anode material. Wherein, the elemental Si content in the silicon waste described in step S1 is ≥80wt%.
[0007] Furthermore, in the preparation method, the particle size of the silicon waste, the silicon dioxide, and the metallic manganese in step S1 is independently 0.1~20μm.
[0008] Furthermore, in the preparation method, the mass ratio of silicon waste to silicon dioxide in step S1 is 1:1.8~2; The mass ratio of the sum of the silicon waste and silicon dioxide in step S1 to the mass of the metallic manganese is 1:0.02~0.1.
[0009] Furthermore, in the preparation method, after the silicon waste, silicon dioxide and manganese metal are mixed in step S1, a binder and water are added and mixed again, and then pressed into shape.
[0010] Furthermore, in the preparation method, the drying temperature in step S1 is 60~100℃ and the time is 6~12h.
[0011] Furthermore, in the preparation method, the vacuum degree of the vacuum condition in step S2 is 0.01~10 Pa.
[0012] Furthermore, in the preparation method, the heat preservation temperature for heat preservation vaporization in step S2 is 1300~1450℃, the heat preservation time is 0.5~3h, and the heating rate to the required heat preservation temperature is 5~10℃ / min. The holding temperature for the condensation deposition in step S2 is 300~600℃, and the holding time is 0.5~3h.
[0013] Furthermore, in the preparation method, after the condensation deposition in step S2, the product obtained by condensation deposition is crushed to obtain in-situ manganese-doped modified silicon-oxygen anode material. The particle size D of the in-situ manganese-doped modified silicon-oxygen anode material described in step S2 100 ≤9μm.
[0014] The present invention also provides an in-situ manganese-doped modified silicon-oxygen anode material, wherein the manganese content of the in-situ manganese-doped modified silicon-oxygen anode material is 1~12wt%.
[0015] This invention also provides an application of in-situ manganese-doped modified silicon-oxygen anode material in lithium-ion batteries.
[0016] As can be seen from the above technical solution, compared with the prior art, the present invention has the following beneficial effects: This invention provides a method for preparing in-situ manganese-doped modified silicon-oxygen anode material. Silicon waste, silicon dioxide, and metallic manganese (Mn) are uniformly mixed, shaped, and dried. The mixture is then heated under vacuum conditions, causing the silicon waste to react with silicon dioxide to generate SiO vapor. Metallic Mn migrates simultaneously and co-condenses with the SiO vapor, resulting in an in-situ manganese-doped modified SiO composite anode material. In the prepared material, Mn is dispersed within the SiO matrix, forming a manganese-containing silicate phase and a manganese-silicon alloy phase. The manganese-containing silicate phase can regulate the Si-O structure, reduce irreversible lithium consumption during the initial lithium insertion process, mitigate volume changes, enhance structural stability, and improve cycle life. The manganese-silicon alloy phase can improve electron transport capability, thereby improving the material's initial coulombic efficiency and cycle performance. In other words, Mn participates in the reaction in-situ during SiO formation, forming a specific Mn-Si-O / Mn-Si structural phase, altering the internal structure and composition of the SiO material, thus producing a structural regulation effect different from simple doping. Compared with existing technologies, the method of the present invention is simple, low-cost, and has a high SiO yield. Moreover, the resulting material can simultaneously improve the initial coulombic efficiency and cycle stability, making it suitable for lithium-ion battery anode materials. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below.
[0018] Figure 1 The image shows the XRD pattern of the in-situ Mn-modified SiO composite anode material of Example 1. Figure 2 Here is a SEM image of the in-situ Mn-modified SiO composite anode material from Example 1; Figure 3 This is a TEM image of the in-situ Mn-modified SiO composite anode material of Example 1; Figure 4 The graph shows the discharge cycle performance of the battery obtained in Example 1. Detailed Implementation
[0019] This invention provides a method for preparing an in-situ manganese-doped modified silicon-oxygen anode material, comprising the following steps: S1. Silicon waste, silicon dioxide and metallic manganese are mixed, pressed into a preform, and dried to obtain a pre-reaction mixture; S2. Under vacuum conditions, the pre-reaction mixture is sequentially subjected to heat preservation vaporization and condensation deposition to obtain in-situ manganese-doped modified silicon-oxygen anode material. Wherein, the elemental Si content in the silicon waste described in step S1 is ≥80wt%.
[0020] In this invention, the specific source of the silicon waste in step S1 is not specifically limited, as long as it contains a certain proportion of elemental Si and can participate in the reaction. Specifically, the silicon waste includes one or more of the following: silicon cutting waste from the photovoltaic industry, silicon processing waste from the semiconductor industry, silicon powder waste from the industrial silicon production process, and recycled silicon materials from photovoltaic modules.
[0021] In this invention, the sources of silicon cutting waste in the photovoltaic industry are: diamond wire cutting waste generated during the production of solar-grade silicon wafers, and waste generated during the cutting and grinding of monocrystalline silicon or polycrystalline silicon rods; the composition of silicon cutting waste in the photovoltaic industry includes: elemental Si 85~98wt%, SiO2 1~8wt%, and other impurities 0.1~5wt% (SiC, Fe, Al, Ca, etc.). Sources of silicon processing waste in the semiconductor industry: scraps, fragments, or silicon powder generated during the processing of single-crystal silicon wafers, wafer dicing, chamfering, grinding, and polishing; The composition of silicon processing waste in the semiconductor industry includes: elemental Si 90~99wt%, SiO2 0.5~5wt%, and other impurities 0.01~1wt% (trace impurities such as B, P, Fe, and Cu); Sources of silicon powder waste in industrial silicon production: fine silicon powder generated during industrial silicon smelting, crushing, screening and processing; composition of silicon powder waste in industrial silicon production includes: elemental Si 80~95wt%, SiO2 2~15wt%, and other impurities 0.5~5wt% (SiC, Fe, Al, Ca and other impurities); The sources of recycled silicon materials for photovoltaic modules are: silicon wafer fragments or recycled silicon powder obtained from the dismantling and recycling of waste solar cell modules; the composition of recycled silicon materials for photovoltaic modules includes: elemental Si 80~95wt%, SiO2 1~10wt%, and other impurities 0.5~5wt% (Ag, Al, glass residues and other impurities).
[0022] Silicon waste refers to waste silicon materials generated during industrial production processes containing elemental silicon. Its main function is to serve as a silicon source, reacting with silicon dioxide under vacuum and high-temperature conditions to generate SiO vapor.
[0023] In this invention, the particle size of the silicon waste, silicon dioxide, and metallic manganese in step S1 is preferably 0.1~20 μm. The method for obtaining this particle size is not limited; crushing, grinding, or other processes well-known in the art can be used.
[0024] The purpose of using raw materials with a particle size of 0.1~20μm is to ensure thorough mixing with silicon dioxide and metallic manganese.
[0025] In this invention, the mass ratio of silicon waste to silicon dioxide in step S1 is preferably 1:1.8~2, more preferably 1:1.85~1.95, and even more preferably 1:1.9.
[0026] In this invention, the mass ratio of the sum of the silicon waste and silicon dioxide in step S1 to the mass of the metallic manganese is preferably 1:0.02~0.1, more preferably 1:0.03~0.08, and even more preferably 1:0.05.
[0027] In this invention, after the silicon waste, silicon dioxide and metallic manganese are mixed in step S1, a binder and water are added and mixed again before pressing and molding. The adhesive preferably includes one or more of polyvinyl alcohol, sodium carboxymethyl cellulose, and polyvinylpyrrolidone, more preferably polyvinyl alcohol or sodium carboxymethyl cellulose, and more preferably polyvinyl alcohol. The mass of the binder is preferably 0.5-8% of the total mass of silicon waste, silicon dioxide, and metallic manganese, more preferably 1-5%, and even more preferably 2-3%. The water is preferably 5-25% of the total mass of silicon waste, silicon dioxide, and metallic manganese, more preferably 8-20%, and even more preferably 10-15%.
[0028] The purpose of adding binder and water is as follows: The binder is mainly used to improve the strength and structural stability of the preform after the premixed reaction mixture is pressed, making the preform less prone to pulverization or collapse during drying, heating, and vacuum reaction; the water is mainly used to adjust the wettability and plasticity of the mixture, facilitating pressing and molding. Generally, there are no special limitations; as long as the mixture can be molded, it is acceptable. When the amount of binder or water added is too low, the mixture will lack moldability, and the preform will easily become loose; when the amount of binder or water added is too high, the drying time will be prolonged, and the stability of the subsequent vacuum reaction process will be affected.
[0029] In this invention, the pressing molding in step S1 is preferably room temperature molding; the room temperature is not particularly limited, 15~25℃ is sufficient; the pressing pressure is preferably 2~50MPa, more preferably 5~30MPa, and even more preferably 10~20MPa; the holding time is preferably 0.5~10min, more preferably 1~5min, and even more preferably 2~3min.
[0030] The purpose of compression molding is to form a preform with a certain mechanical strength from silicon waste, silicon dioxide, metallic manganese, binder, and water, to prevent the powder from becoming loose during drying, transfer, and vacuum heating, to increase the contact between raw materials, and to ensure that silicon waste and silicon dioxide can fully react to generate SiO vapor under subsequent vacuum and high temperature conditions. At the same time, it promotes the volatilization and migration of metallic manganese and co-condenses and deposits with SiO vapor, thereby achieving in-situ doping of manganese in the SiO matrix, while retaining appropriate pores or channels to facilitate the subsequent generation, migration, and co-condensation and deposition of SiO vapor and Mn vapor.
[0031] In this invention, the macroscopic morphology of the embryo in step S1 includes, but is not limited to, cylindrical, sheet-like, plate-like, spherical, porous block-like, or other molded structures that can maintain structural stability and meet reaction requirements. The example is a honeycomb-shaped (a type of porous block) structure.
[0032] In this invention, the drying temperature in step S1 is preferably 60~100℃, more preferably 80~100℃, and even more preferably 90℃; the drying time is preferably 6~12h, more preferably 8~12h, and even more preferably 10h.
[0033] In this invention, step S2 is preferably carried out in a vacuum device, heat preservation vaporization is carried out in the reaction zone of the device, and condensation deposition is carried out in the deposition zone of the device.
[0034] In this invention, the vacuum degree of the vacuum condition described in step S2 is preferably 0.01~10 Pa, more preferably 0.5~2 Pa, and even more preferably 1 Pa.
[0035] In this invention, the heat preservation temperature for heat preservation vaporization in step S2 is preferably 1300~1450℃, more preferably 1350~1400℃, and even more preferably 1350℃; the heat preservation time is preferably 0.5~3h, more preferably 1~1.5h, and even more preferably 1h; the heating rate to the required heat preservation temperature is preferably 5~10℃ / min, more preferably 7~10℃ / min, and even more preferably 8℃ / min.
[0036] In this invention, the heat preservation temperature for condensation deposition in step S2 is preferably 300~600℃, more preferably 400~500℃, and even more preferably 450℃; the heat preservation time is preferably 0.5~3h, more preferably 1~1.5h, and even more preferably 1h.
[0037] In this invention, the pre-reaction mixture is placed in the reaction zone of a vacuum device, heated at a certain heating rate, and the reaction temperature is controlled and kept at a certain temperature for a period of time, so that silicon waste reacts with silicon dioxide to generate SiO vapor, while metal Mn volatilizes and migrates. While keeping the temperature, a condensation temperature is set in the deposition zone so that SiO vapor and manganese vapor condense and deposit together, and then the condensation product is collected by natural cooling.
[0038] In this invention, after the condensation deposition in step S2, the product obtained by condensation deposition is crushed to obtain in-situ manganese-doped modified silicon-oxygen anode material.
[0039] In this invention, the crushing device is preferably an air jet crusher. There are no special limitations on the crushing conditions; the particle size of the crushed material only needs to meet the requirements.
[0040] In this invention, the particle size D of the in-situ manganese-doped modified silicon-oxygen anode material described in step S2 is... 100 Preferably ≤9μm.
[0041] The present invention also provides an in-situ manganese-doped modified silicon-oxygen anode material, wherein the manganese content of the in-situ manganese-doped modified silicon-oxygen anode material is preferably 1~12wt%, more preferably 3.1~8.8wt%, and more preferably 4.6wt%.
[0042] This invention also provides an application of in-situ manganese-doped modified silicon-oxygen anode material in lithium-ion batteries.
[0043] In this invention, the method of application is not limited, and any solution well known in the art can be used.
[0044] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0045] Example 1
[0046] This embodiment provides a method for preparing an in-situ Mn-modified SiO composite anode material, comprising the following steps: S1. Take 100g of micron-sized silicon cutting waste from the photovoltaic industry (94wt% Si, 4wt% SiO2, 2wt% other impurities), 190g of micron-sized silica, and 14.5g of micron-sized Mn powder. The particle size of the silicon waste, silica, and Mn powder is 0.1~20μm. After mixing the above raw materials evenly, add 6.1g of polyvinyl alcohol (PVA-1799 type, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., item number P105126) and 36.5g of deionized water to mix. Press the mixture into a honeycomb-shaped preform at 15MPa at room temperature, hold the pressure for 2min, and dry at 80℃ for 10h to obtain the pre-reaction mixture.
[0047] S2. Place the pre-reaction mixture in the reaction zone of a vacuum furnace, evacuate to 1 Pa, and heat to 1350℃ at a rate of 8℃ / min, holding for 1 hour; simultaneously, maintain the deposition zone temperature at 450℃ for 1 hour. During the holding process, silicon waste reacts with silicon dioxide to generate SiO vapor, and metallic Mn volatilizes, migrates, and condenses and deposits together with the SiO vapor. After the holding period, allow natural cooling, collect the condensed products from the deposition zone, and then perform airflow crushing to ensure the resulting powder particle size meets the D... 100 ≤9μm, and in-situ Mn-modified SiO composite anode material was obtained with Mn content of 4.6wt%.
[0048] The XRD pattern of the in-situ Mn-modified SiO composite anode material prepared in Example 1 is shown below. Figure 1 As shown, the material as a whole exhibits a structural characteristic dominated by amorphous phases.
[0049] SEM image of the in-situ Mn-modified SiO composite anode material prepared in Example 1 is shown below. Figure 2 As shown in the figure, the prepared silica suboxide particles are uniform in size.
[0050] TEM image of the in-situ Mn-modified SiO composite anode material prepared in Example 1 is shown below. Figure 3 As shown in the figure, it can be seen that the modified silicon suboxide matrix contains a uniformly distributed typical manganese silicate phase and a manganese silicon alloy phase, which respectively enhance the initial coulombic efficiency and cycle stability.
[0051] Example 2
[0052] This embodiment provides a method for preparing an in-situ Mn-modified SiO composite anode material, comprising the following steps: S1. Take 100g of micron-sized semiconductor industry silicon processing waste (97wt% elemental Si, 2.5wt% SiO2, and 0.5wt% other impurities), 180g of micron-sized silica, and 5.6g of micron-sized metallic Mn powder. The particle size of the raw materials is controlled between 0.1 and 20μm. After mixing the above raw materials evenly, add 2.9g of sodium carboxymethyl cellulose binder (low viscosity type, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., item number C299502) and 22.8g of deionized water. Press the mixture into a honeycomb-shaped preform at 5MPa at room temperature, hold the pressure for 1min, and dry at 85℃ for 12h to obtain the pre-reaction mixture.
[0053] S2. The pre-reaction mixture is placed in the reaction zone of a vacuum furnace, with the vacuum level controlled at 10 Pa. The temperature is increased to 1300℃ at a rate of 5℃ / min and held for 0.5 h. The temperature in the deposition zone is controlled at 600℃ and held for 0.5 h. The SiO vapor and manganese vapor generated during the reaction co-condense and deposit in the deposition zone. After the reaction, the mixture is allowed to cool naturally, and the condensed product is collected and shaped by airflow crushing to ensure the resulting powder particle size meets the requirements of D. 100 ≤9μm, and in-situ Mn-modified SiO composite anode material was obtained with Mn content of 1.8wt%.
[0054] Example 3
[0055] This embodiment provides a method for preparing an in-situ Mn-modified SiO composite anode material, comprising the following steps: S1. Take 100g of silicon powder waste (88wt% elemental Si, 9wt% SiO2, and 3wt% other impurities) from the production process of micron-sized industrial silicon, 200g of micron-sized silica, and 30g of micron-sized Mn powder. The particle size of the silicon waste, silica, and Mn powder is 0.1~20μm. After mixing evenly, add 16.5g of binder polyvinylpyrrolidone (PVP K30, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., item number P274371) and 66.0g of deionized water. Press the mixture into a honeycomb-shaped preform at 30MPa at room temperature, hold the pressure for 5min, and dry at 90℃ for 10h to obtain the pre-reaction mixture.
[0056] S2. The pre-reaction mixture is placed in the reaction zone of a vacuum furnace and heated to 1450℃ at a heating rate of 10℃ / min under a vacuum of 0.01 Pa, and held for 3 hours. The deposition zone temperature is then controlled at 300℃ and held for 3 hours. During the holding stage, the silicon waste reacts with silicon dioxide to generate SiO vapor, while metallic Mn volatilizes and migrates simultaneously, condensing and depositing together with the SiO vapor in the deposition zone. After the reaction is complete, the mixture is allowed to cool naturally, and the condensed product is collected and processed by an airflow crusher to ensure that the resulting powder particle size meets the requirements of D. 100≤9μm, and in-situ Mn-modified SiO composite anode material was obtained with Mn content of 8.8wt%.
[0057] Example 4
[0058] This embodiment provides a method for preparing an in-situ Mn-modified SiO composite anode material, comprising the following steps: S1. Take 100g of micron-sized recycled silicon waste from photovoltaic modules (90wt% elemental Si, 7wt% SiO2, 3wt% other impurities), 195g of micron-sized silica, and 23.6g of micron-sized metallic Mn powder, all with a particle size of 0.1~20μm. After mixing all raw materials evenly, add 9.6g of binder polyvinyl alcohol (PVA-1799 type, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., item number P105126) and 47.8g of deionized water and knead. Press the mixture into a honeycomb-shaped preform at room temperature under a pressure of 20MPa, hold the pressure for 3min, and dry at 80℃ for 8h to obtain the pre-reaction mixture.
[0059] S2. The pre-reaction mixture is placed in the reaction zone of a vacuum furnace and heated to 1400℃ at a rate of 7℃ / min under a vacuum of 0.5 Pa, and held for 2 hours; simultaneously, the temperature of the deposition zone is maintained at 400℃ for 2 hours. During the reaction, SiO vapor and manganese vapor co-condense and deposit in the deposition zone. After the reaction is complete and the mixture has cooled naturally, the deposited product is collected and crushed by airflow to ensure that the resulting powder particle size meets the requirements of D. 100 ≤9μm, and in-situ Mn-modified SiO composite anode material was obtained with Mn content of 7.6wt%.
[0060] Example 5
[0061] This embodiment provides a method for preparing an in-situ Mn-modified SiO composite anode material, comprising the following steps: S1. Take 100g of micron-sized silicon cutting waste from the photovoltaic industry (94wt% Si, 4wt% SiO2, 2wt% other impurities), 185g of micron-sized silica, and 8.6g of micron-sized metallic Mn powder, all with a particle size of 0.1~20μm. After mixing evenly, add 5.9g of sodium carboxymethyl cellulose binder (low viscosity type, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., item number C299502) and 29.4g of deionized water and knead. Press the mixture into a honeycomb-like preform at room temperature under a pressure of 12MPa, hold the pressure for 3min, and dry at 100℃ for 6h to obtain the pre-reaction mixture.
[0062] S2. The pre-reaction mixture is placed in the reaction zone of a vacuum furnace, with the vacuum level controlled at 2 Pa. The temperature is increased to 1380℃ at a heating rate of 6℃ / min and held for 1.5 h. The deposition zone temperature is controlled at 500℃ and held for 1.5 h. Under vacuum conditions, silicon waste reacts with silicon dioxide to generate SiO vapor, and metallic Mn volatilizes simultaneously and co-deposits with the SiO vapor in the deposition zone. After cooling, the deposition product is collected and shaped by airflow crushing to ensure that the resulting powder particle size meets the D... 100 ≤9μm, and in-situ Mn-modified SiO composite anode material was obtained with Mn content of 3.1wt%.
[0063] Example 6
[0064] This embodiment provides a method for preparing an in-situ Mn-modified SiO composite anode material, comprising the following steps: S1. Take 100g of a mixture of micron-sized semiconductor industry silicon processing waste and photovoltaic industry silicon cutting waste in a 1:1 mass ratio (semiconductor industry silicon processing waste composition: elemental Si 97wt%, SiO2 2.5wt%, other impurities 0.5wt%; photovoltaic industry silicon cutting waste composition: elemental Si 94wt%, SiO2 4wt%, other impurities 2wt%), 190g of micron-sized silica, and 17.4g of micron-sized metallic Mn powder. The particle size of the raw materials is controlled between 0.1 and 20μm. After mixing the raw materials evenly, add 9.2g of polyvinyl alcohol (PVA-1799 type, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., item number P105126) and 46.1g of deionized water to mix. Press the mixture into a honeycomb-shaped preform at room temperature under a pressure of 20MPa, hold the pressure for 5min, and dry at 85℃ for 10h to obtain the pre-reaction mixture.
[0065] S2. The pre-reaction mixture was placed in the reaction zone of a vacuum furnace and heated to 1420℃ at a rate of 9℃ / min under a vacuum of 0.1 Pa, and held for 2.5 h. The temperature in the deposition zone was controlled at 350℃ and held for 2.5 h. During the holding process, the generated SiO vapor and manganese vapor condensed and deposited together in the deposition zone. After the reaction was completed, the mixture was allowed to cool naturally, and the condensed products were collected and subjected to airflow crushing to ensure that the resulting powder particle size met the D... 100 ≤9μm, and in-situ Mn-modified SiO composite anode material was obtained with Mn content of 6.1wt%.
[0066] Comparative Example 1
[0067] This comparative example provides a method for preparing an unmodified ordinary silicon powder-based SiO anode material, comprising the following steps: S1. Take 100g of ordinary micron-sized silicon powder (purity ≥99wt%, commercially available industrial micron-sized silicon powder) and 190g of micron-sized silicon dioxide. The particle size of both the ordinary micron-sized silicon powder and silicon dioxide is 0.1~20μm. After mixing the above raw materials evenly, add 5.8g of binder polyvinyl alcohol (PVA-1799 type, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., item number P105126) and 34.8g of deionized water and mix. Press the mixture into a honeycomb-shaped preform at room temperature under a pressure of 15MPa, hold the pressure for 2min, and dry at 80℃ for 10h to obtain the pre-reaction mixture.
[0068] S2. Place the pre-reaction mixture in the reaction zone of a vacuum furnace, evacuate to 1 Pa, and heat to 1350℃ at a rate of 8℃ / min, holding for 1 hour; simultaneously, maintain the deposition zone temperature at 450℃ for 1 hour. During the holding process, ordinary micron-sized silicon powder reacts with silicon dioxide to generate SiO vapor, which condenses and deposits in the deposition zone. After the holding period, allow natural cooling, collect the condensed product from the deposition zone, and then perform airflow crushing to ensure the resulting powder particle size meets the D... 100 ≤9μm, thus obtaining unmodified ordinary silicon powder-based SiO anode material.
[0069] Comparative Example 2
[0070] This comparative example provides a method for preparing an in-situ Mn-modified ordinary silicon powder-based SiO composite anode material, comprising the following steps: S1. Take 100g of ordinary micron-sized silicon powder (purity ≥99wt%, commercially available industrial micron-sized silicon powder), 190g of micron-sized silica, and 14.5g of micron-sized metallic Mn powder. The particle size of the ordinary micron-sized silicon powder, silica, and metallic Mn powder are all 0.1~20μm. After mixing the above raw materials evenly, add 5.8g of binder polyvinyl alcohol (PVA-1799 type, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., item number P105126) and 34.8g of deionized water and mix. Press the mixture into a honeycomb-shaped preform at room temperature under a pressure of 15MPa, hold the pressure for 2min, and dry at 80℃ for 10h to obtain the pre-reaction mixture.
[0071] S2. Place the pre-reaction mixture in the reaction zone of a vacuum furnace, evacuate to 1 Pa, and heat to 1350℃ at a rate of 8℃ / min, holding for 1 hour; simultaneously, maintain the deposition zone temperature at 450℃ for 1 hour. During the holding process, ordinary micron-sized silicon powder reacts with silicon dioxide to generate SiO vapor, while metallic Mn volatilizes and migrates simultaneously, condensing and depositing together with the SiO vapor in the deposition zone. After the holding period, allow natural cooling, collect the condensed products from the deposition zone, and then perform airflow crushing to ensure the resulting powder particle size meets the D... 100 ≤9μm, and in-situ Mn-modified ordinary silicon powder-based SiO composite anode material was obtained, with a Mn content of 4.5wt%.
[0072] Comparative Example 3
[0073] This comparative example provides a method for preparing an unmodified waste silicon powder-based SiO anode material, comprising the following steps: S1. Take 100g of micron-sized silicon cutting waste from the photovoltaic industry (94wt% elemental Si, 4wt% SiO2, and 2wt% other impurities) and 190g of micron-sized silica. The particle size of both the silicon waste and silica is 0.1~20μm. After mixing the above raw materials evenly, add 5.8g of binder polyvinyl alcohol (PVA-1799 type, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., item number P105126) and 34.8g of deionized water and knead. Press the mixture into a honeycomb-shaped preform at room temperature under a pressure of 15MPa, hold the pressure for 2min, and dry at 80℃ for 10h to obtain the pre-reaction mixture.
[0074] S2. Place the pre-reaction mixture in the reaction zone of a vacuum furnace, evacuate to 1 Pa, and heat to 1350℃ at a rate of 8℃ / min, holding for 1 hour; simultaneously, maintain the deposition zone temperature at 450℃ for 1 hour. During the holding process, silicon waste reacts with silicon dioxide to generate SiO vapor, which condenses and deposits in the deposition zone. After the holding period, allow natural cooling, collect the condensed product from the deposition zone, and then perform airflow crushing to ensure the resulting powder particle size meets the D... 100 ≤9μm, resulting in unmodified waste silicon powder-based SiO anode material.
[0075] Application Examples 1-6, Comparison with Application Examples 1-3
[0076] The in-situ Mn-modified SiO composite anode material prepared in Example 1 was directly used to prepare lithium-ion battery anode materials. The anode preparation method was as follows: the in-situ Mn-modified SiO composite anode material, Super P-conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber were mixed in a mass ratio of 80:10:5:5. Deionized water was added and stirred to form a uniform slurry. The resulting slurry was uniformly coated on the surface of a copper foil current collector, dried under vacuum at 80°C for 12 hours, rolled, and cut into circular electrode sheets. The electrodes were then dried under vacuum at 120°C for 12 hours to obtain the negative electrode. The prepared negative electrode, Celgard 2500 microporous membrane, and fresh lithium foil were used as the working electrode, separator, and counter electrode, respectively. The electrolyte was 1.0 M LiPF6 dissolved in ethylene carbonate / dimethyl carbonate / diethyl carbonate (EC / DMC / DEC, volume ratio 1:1:1), with 5% fluoroethylene carbonate (FEC) added. The batteries were assembled into CR2032 button batteries in an argon-protected glove box as application example 1.
[0077] Application Examples 2-6 and Comparative Examples 1-3 are prepared using the same methods as Application Example 1, except that they are replaced with the negative electrode materials of Examples 2-6 and Comparative Examples 1-3, respectively.
[0078] Performance tests were conducted on batteries prepared in comparison with those prepared in Examples 1-6 and Application Examples 1-3. The charge-discharge tests were performed at 0.1 A·g for the first three cycles. -1 The rate is increased by a factor of 1, and subsequent cycles are performed at 1 A·g. -1 The voltage range is 0.01~2V (relative to Li). + / Li).
[0079] The discharge cycle performance curve of the battery obtained in Example 1 is as follows: Figure 4 As shown, the yield of the in-situ Mn-modified SiO composite anode material prepared in Example 1 was 94%. (The yield is the ratio of the actual mass of the in-situ Mn-modified SiO composite anode material collected after condensation deposition to the theoretical mass of the SiO-based composite product.) The initial coulombic efficiency of Application Example 1 was 78%, which was achieved at 1 A·g -1 After 100 cycles under the specified current, the capacity remains at 917mAh / g.
[0080] The in-situ Mn-modified SiO composite anode material prepared in Example 2 had a yield of 93%. Application Example 2 showed an initial coulombic efficiency of 74%, and its cycle performance was at 1 A·g. -1 After 100 cycles at a given current, the capacity is 842mAh / g.
[0081] The in-situ Mn-modified SiO composite anode material prepared in Example 3 had a yield of 91%. In Application Example 3, the initial coulombic efficiency was 75%, and its cycle performance was at 1 A·g. -1 After 100 cycles under a certain current, the capacity is 865mAh / g.
[0082] The in-situ Mn-modified SiO composite anode material prepared in Example 4 had a yield of 95%. Application Example 4 showed an initial coulombic efficiency of 77%, and its cycle performance was at 1 A·g. -1 After 100 cycles under the specified current, the capacity is 906mAh / g.
[0083] The in-situ Mn-modified SiO composite anode material prepared in Example 5 had a yield of 95%. Application Example 5 showed an initial coulombic efficiency of 72%, and its cycle performance was at 1 A·g. -1 After 100 cycles under the specified current, the capacity is 859mAh / g.
[0084] The in-situ Mn-modified SiO composite anode material prepared in Example 6 had a yield of 92%. The initial coulombic efficiency of Application Example 6 was 74%, and its cycle performance was [value missing] at 1 A·g [value missing]. -1 After 100 cycles under a certain current, the capacity is 895mAh / g.
[0085] The unmodified ordinary silicon powder-based SiO anode material prepared in Comparative Example 1 had a yield of 79%. In contrast, Application Example 1 showed an initial coulombic efficiency of 63% and a cycle performance of 1 A·g. -1 After 100 cycles at a given current, the capacity is 212mAh / g.
[0086] The in-situ Mn-modified ordinary silicon powder-based SiO composite anode material prepared in Comparative Example 2 had a yield of 80%. In contrast, Application Example 2 showed an initial coulombic efficiency of 76%, and its cycle performance was at 1 A·g. -1 After 100 cycles under a certain current, the capacity is 895mAh / g.
[0087] The unmodified waste silicon powder-based SiO anode material prepared in Comparative Example 3 had a yield of 94%. In contrast, Application Example 3 had an initial coulombic efficiency of 64% and its cycle performance was [not specified in the original text]. -1 After 100 cycles at a given current, the capacity is 196mAh / g.
[0088] The main reason for the poor electrochemical performance of the comparative examples is the lack of an effective in-situ Mn modification structure or insufficient uniformity of modification. Comparative Examples 1 and 3 did not add Mn, resulting in SiO materials with inherently poor electronic conductivity. During the initial lithiation process, numerous irreversible side reactions occurred, easily consuming active lithium and forming an unstable SEI film, thus leading to low initial coulombic efficiency. Simultaneously, the large volume change of the SiO-based material during cycling easily caused particle pulverization, electrode structure damage, and conductive contact failure, resulting in significant capacity decay during cycling.
[0089] In Examples 1-6, metallic Mn volatilizes and migrates simultaneously during the heat preservation vaporization process, and co-condenses and deposits with SiO vapor, allowing Mn to be more uniformly dispersed in the SiO matrix and forming a manganese silicate phase and a manganese-silicon alloy phase. The manganese silicate phase can stabilize the SiO matrix structure to a certain extent, reduce the consumption of active lithium by irreversible side reactions during the first lithiation, thereby improving the first coulombic efficiency. At the same time, it buffers the volume change of the silicon-oxygenated material and inhibits particle pulverization and electrode structure damage during cycling. The manganese-silicon alloy phase is beneficial to improving the internal electron transport of the material. Therefore, the materials in these examples exhibit high first coulombic efficiency and good cycling stability.
[0090] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing an in-situ manganese-doped modified silicon-oxygen anode material, characterized in that, Includes the following steps: S1. Silicon waste, silicon dioxide and metallic manganese are mixed, pressed into a preform, and dried to obtain a pre-reaction mixture; S2. Under vacuum conditions, the pre-reaction mixture is sequentially subjected to heat preservation vaporization and condensation deposition to obtain in-situ manganese-doped modified silicon-oxygen anode material. Wherein, the elemental Si content in the silicon waste described in step S1 is ≥80wt%.
2. The preparation method according to claim 1, characterized in that, The silicon waste, silicon dioxide, and metallic manganese in step S1 have independent particle sizes of 0.1~20μm.
3. The preparation method according to claim 1 or 2, characterized in that, The mass ratio of silicon waste to silicon dioxide in step S1 is 1:1.8~2; The mass ratio of the sum of the silicon waste and silicon dioxide in step S1 to the mass of the metallic manganese is 1:0.02~0.
1.
4. The preparation method according to claim 3, characterized in that, After the silicon waste, silicon dioxide and manganese metal mentioned in step S1 are mixed, a binder and water are added and mixed again, and then pressed into shape.
5. The preparation method according to claim 3, characterized in that, The drying temperature in step S1 is 60~100℃, and the time is 6~12h.
6. The preparation method according to claim 1, characterized in that, The vacuum degree of the vacuum condition described in step S2 is 0.01~10 Pa.
7. The preparation method according to claim 1 or 6, characterized in that, The heat preservation temperature for heat preservation vaporization in step S2 is 1300~1450℃, the heat preservation time is 0.5~3h, and the heating rate to the required heat preservation temperature is 5~10℃ / min. The holding temperature for the condensation deposition in step S2 is 300~600℃, and the holding time is 0.5~3h.
8. The preparation method according to claim 1, characterized in that, After the condensation deposition described in step S2, the product obtained by condensation deposition is crushed to obtain in-situ manganese-doped modified silicon-oxygen anode material. The particle size D of the in-situ manganese-doped modified silicon-oxygen anode material described in step S2 100 ≤9μm.
9. An in-situ manganese-doped modified silicon-oxygen anode material prepared by the preparation method according to any one of claims 1 to 8, characterized in that, The manganese content of the in-situ manganese-doped modified silicon-oxygen anode material is 1~12wt%.
10. The application of the in-situ manganese-doped modified silicon-oxygen anode material as described in claim 9 in lithium-ion batteries.
